First record of Aspergillus caelatus as a pathogen of Heterotrigona itama and Geniotrigona thoracica in Malaysia - Amirthalingam, Vinailosni; Ataa, Nur Syuhada Mohd; Mahmuddin, Siti Sarah; Adam, Nur Azura; Nai, Yu-Shin; Lau, Wei-Hong (Elsevier, 2023)
Heterotrigona itama and Geniotrigona thoracica become popular in Malaysia as honey producer in the 21st century. Like other bee species, stingless bees can be infected by pathogens. Disease-related population declines may affect honey production, agricultural productivity, and biodiversity. Thus, this study aimed to evaluate the health status of stingless bee colonies in selected bee farms in Malaysia. Adults Heterotrigona itama and Geniotrigona thoracica were collected from 79 colonies in 9 farms and screened for known pathogens of honey bees and stingless bees using 15 primer sets. All results were negative, indicating the absence of these pathogens in the bee specimens. During the bee sampling at Infoport Halal Hub UPM, we encountered a collapsed colony of H. itama. A fungal isolate was isolated and confirmed to be Aspergillus caelatus. Virulence tests revealed that A. caelatus exhibited high virulence to both H. itama and G. thoracica. Infected larvae became lethargic after 1–2 day after treatment (DAT) with white mycelium developed on their integument. The fungus caused 100 larval mortality in both H. itama and G. thoracica after 8 DAT, with LC50 values of 7.58 × 103 conidia/µl and 6.24 × 103 conidia/µl respectively. Yellow-green conidia were observed on the cadavers. A. caelatus demonstrated high virulence towards both H. itama and G. thoracica, leading to severe larval mortality. This study represents the first documented case of a disease infecting stingless bees in Malaysia. Future research is needed to assess the prevalence of A. caelatus in various stingless bee species and other pollinators within the country. © 2023 Korean Society of Applied Entomology